EFEKTIVITAS PEMBERIAN KOTORAN KANDANG SAPI DAN PUPUK ORGANIK CAIR KULIT PISANG PADA PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT CERI (Lycopersicum Esculentum Mill) - Ramadani, Jun; Sembiring, Desi Sri Pasca Sari (Fakultas Pertanian, Universitas Janabadra, 2024)
The aim of this research was to determine the effectiveness of cow dung fertilizer and banana peel liquid organic fertilizer on the growth and production of cherry tomatoes. This research used a factorial randomized block design (RAK) consisting of 2 factors with 12 treatment combinations and 3 replications so that 36 plots were needed in the study. The first factor examined was the treatment of cow dung fertilizer with the symbol